Experimental and numerical analysis of the oxidative decomposition of H2S. (15th June 2017) - Barba, D.; Cammarota, F.; Vaiano, V.; Salzano, E.; Palma, V.
Highlights: A preliminary chemical kinetic model for H2 S oxidation has been developed. Experimental data were compared with model results at different operating conditions. H2 yield, SO2 selectivity of the model are higher than the experimental data at 900 °C. The model predictions at 1100 °C are in good agreement with the experimental values. The model should be revised and optimized to fit better to the experimental results. Abstract: Recent environmental and economic considerations have made the focus of attention new treatment processes of the residual (tail) gas of Claus plants, based on the oxidative decomposition of H2 S to Sulphur and Hydrogen, In this work, the thermal, oxidative decomposition of H2 S in an homogeneous phase has been studied by developing a comprehensive chemical kinetic model for the oxidation of H2 S in a low oxygen atmosphere, by varying the O2 /H2 S ratio (0.2–0.35), residence time (150–300 ms), and process temperatures (900–1100 °C). The kinetic model has been developed by combining existing models for the oxidation of H2 S, with no tuning of the parameters or kinetic constants and validated in relation to the experimental data. The results show a very good agreement with the experimental values at higher temperatures (1100 °C). At 900 °C, the H2 S conversion is well predicted by the model, whereas the H2 yield and SO2 selectivity are consistently higher than the experimental values. A sensitivity analysis for the complex kinetic system has highlighted the importance of the reaction (O2 + S ↔ O + SO) at lower temperatures.